Evaluasi Kualitas Air Kali Petukangan di Sekitar Kawasan Industri Pulogadung Berdasarkan Parameter Fisika dan Kimia - Adia Putra Wirman; Ichsan Riyanto; Tri Prasetiyorin; Nurul Nikmatullah; Oktadio Erikardo; Euis Purbasari (Jurnal Sintesis: Penelitian Sains, Terapan dan Analisisnya, 2026)
Kali Petukangan is a small river stream located on Jalan Rawa Gelam, Cakung District, East Jakarta. This river is frequently used as a disposal site for both domestic and industrial waste, largely due to its proximity to the Pulogadung industrial area. This study aims to evaluate the water quality of Kali Petukangan by analyzing several physical and chemical parameters. The research process includes determining sampling points, collecting and transporting samples, conducting laboratory tests, and analyzing the data. The study employs a laboratory experimental design with a descriptive observational approach and a sequential explanatory method. The test results indicate that the average water temperature is 26°C, pH ranges from 7.59 to 8.30, color varies from 3.0 to 57.0 Pt-Co, conductivity ranges between 643 and 763 µmhos/cm, total dissolved solids (TDS) are between 313.3 and 453.3 mg/L, total suspended solids (TSS) range from 47.5 to 73 mg/L, dissolved oxygen (DO) ranges from 0.39 to 2.75 mg/L, and biological oxygen demand (BOD) is between 16.55 and 27.50 mg/L. Based on these results, the water quality of Kali Petukangan is classified as moderately polluted.